Assessment of lung cell toxicity of various gasoline engine exhausts using a versatile in vitro exposure system. (April 2018) - Bisig, Christoph; Comte, Pierre; Güdel, Martin; Czerwinski, Jan; Mayer, Andreas; Müller, Loretta; Petri-Fink, Alke; Rothen-Rutishauser, Barbara
Abstract: Adverse effect studies of gasoline exhaust are scarce, even though gasoline direct injection (GDI) vehicles can emit a high number of particles. The aim of this study was to conduct an in vitro hazard assessment of different GDI exhausts using two different cell culture models mimicking the human airway. In addition to gasoline particle filters (GPF), the effects of two lubrication oils with low and high ash content were assessed, since it is known that oils are important contributors to exhaust emissions. Complete exhausts from two gasoline driven cars (GDI1 and GDI2) were applied for 6 h (acute exposure) to a multi-cellular human lung model (16HBE14o-cell line, macrophages, and dendritic cells) and a primary human airway model (MucilAir™). GDI1 vehicle was driven unfiltered and filtered with an uncoated and a coated GPF. GDI2 vehicle was driven under four settings with different fuels: normal unleaded gasoline, 2% high and low ash oil in gasoline, and 2% high ash oil in gasoline with a GPF. GDI1 unfiltered was also used for a repeated exposure (3 times 6 h) to assess possible adverse effects. After 6 h exposure, no genes or proteins for oxidative stress or pro-inflammation were upregulated compared to the filtered air control in both cell systems, neither in GDI1 with GPFs nor in GDI2 with the different fuels. However, the repeated exposure led to a significant increase in HMOX1 and TNFa gene expression in the multi-cellular model, showing the responsiveness of the system towards gasoline engine exhaust upon prolonged exposure. The reduction of particles by GPFs is significant and no adverse effects were observed in vitro during a short-term exposure. On the other hand, more data comparing different lubrication oils and their possible adverse effects are needed. Future experiments also should, as shown here, focus on repeated exposures. Graphical abstract: Image 1 Highlights: GPFs significantly reduce particle number from gasoline engines. No oxidative stress or pro-inflammation upon acute (6 h) exposure. HMOX1 and TNFa upregulated after repeated (3 × 6 h) exposure. Two cell culture models mimicking the human airway showed the same effects. Abstract : An acute exposure of 6 different GDI exhausts has no effect on two different lung cell models, but a repeated exposure shows oxidative stress and pro-inflammation.